A Study of Non-Physical Interior Elements in Shaping Sense of Place in Airport Executive Lounges: A Case Study of Concordia Lounge, I Gusti Ngurah Rai International Airport - Salmannida, Nisriina; Wahyudie , Prasetyo (International Journal of Social Service and Research, 2025)
As a premier tourist destination and an important transit hub in Indonesia, Bali requires airport waiting facilities that are not only functional but also comfortable and meaningful. The Concordia Lounge at I Gusti Ngurah Rai International Airport serves as an exclusive space that offers such an experience. This study aims to examine how non-physical interior elements—such as emotional comfort, perception of facilities, and integration of local culture—shape the sense of place and enhance user satisfaction. Using a qualitative approach through observation and semi-structured interviews, this research explores users’ perceptions of spatial atmosphere and emotional attachment to the place. The findings indicate that emotional comfort and facility quality are dominant factors influencing user experience. A tranquil atmosphere, privacy, cleanliness, seating comfort, and personalized service contribute to emotional attachment. Elements such as warm lighting, incense scents, and traditional decorations reinforce the local Balinese ambiance. This study highlights the importance of non-physical elements in creating a waiting space that is not only functionally comfortable but also emotionally engaging through user experience design and place-making approaches. These findings provide insights for lounge operators to improve service quality based on user experience. These insights demonstrate the strategic importance of non-physical elements in designing executive lounges that support user experience, enhance spatial identity, and reinforce the overall image of airport services.